Fatores que afetam a satisfação e a fidelidade do cliente: um estudo com compradores de automóveis - Lira, Janiere de (2006)
This thesis presents a contribution to the study customer satisfaction models, analyzing the relationship between antecedent variables satisfaction and customer loyalty, through a survey with car s buyers in Natal. The theorical survey is focused in concepts of customer satisfaction and loyalty, and in the customer satisfaction index models. For the field survey, was applied a questionnaire, based on the Norwegian Customer Satisfaction Barometer (NCSB), considered by Johnson et al. (2001), with 106 customer of concessionary Fiat, the Pontanegra Automóveis. The main results obtained by the multiple regression analysis reveal that, considering the Fiat, the satisfaction is influencing by reliance degree in the firm seriousness and by complaining handling, the loyalty is influenced by possibility of again pay the same value if was again buy a car, the satisfaction degree with a car, affective commitment relationship firm customer of the own car and the complaining handling. Considering the concessionaire, the satisfaction is influenced by reliance degree in the firm seriousness, ability degree of the concessionaire in delivery service and by complaining handling, already the loyalty is influencing by possibility of again pay the same value if was again buy a car, affective commitment relations to be concessionaire s customer, by calculate commitment in relation the economic loss of bought this car of this firm and complaining handling